Efficient Control of Population Structure in Model Organism Association Mapping - Kang, Hyun Min; Zaitlen, Noah A.; Wade, Claire M.; Kirby, Andrew; Heckerman, David; Daly, Mark J.; Eskin, Eleazar (Genetics, 2008)
Genomewide association mapping in model organisms such as inbred mouse strains is a promising approach for the identification of risk factors related to human diseases. However, genetic association studies in inbred model organisms are confronted by the problem of complex population structure among strains. This induces inflated false positive rates, which cannot be corrected using standard approaches applied in human association studies such as genomic control or structured association.